Reasons and instruments for preparation of redesigned financial statements - Milačić Srećko; Pavlović Miloš; Đukić Tadija (Ekonomski Pogledi, 2014)
Errors ares not rare in financial accounting process. These errors can be random but also intentional. Intentional errors are deliberately misleading the users of financial information because the image of business enterprises displays different than what it actually is. For this reason there is a need developing of instruments that detect these errors and possible fraud and force the subject of reporting on this basis to draw redesigned financial report that will adapt to real situation. In this paper we will discuss about the reasons for compiling redesigned financial statements and instruments that provide this. Also, in the case of 'Zorex Pharma' Sabac we will show how it looks.